LEARNING AUTONOMY AND ITS SIGNIFICANCE FOR INDONESIAN EFL LEARNERS - Fidyati, Fidyati (STKIP Bina Bangsa Getsempena Banda Aceh, 2017)
The promotion of autonomy-based approaches to language learning has been increasingly applied in many countries, including Indonesia. This paper presents some recent theoretical studies on promoting English as Foreign Language (EFL) independent learning in several countries including Indonesia through the utilization of means and resources. Using media and technology through the Personal Learning Environment (PLE), computer-based materials, portfolio, and exposure to English Language resources has helped students in Switzerland, the United Kingdom, Spain, Portugal, Taiwan, and Indonesia where learning autonomy in English language learning is promoted. The writer also found out significance in promoting learners autonomy regarding Indonesian education practices and socio-cultural beliefs and traditions. The need for autonomy suggests several strategies that should be promoted to Indonesian EFL learners so that their autonomy is well enhanced. This paper argues that autonomous learning is a good model for Indonesian EFL learners and should be considered as a premier strategy to enhance their English proficiency.